Sistema de responsabilidad penal para adolescentes : un sistema entre el garrote y la zanahoria (2021)
The following paper analyzes the existing tensions between the retributive and general prevention purposes of the Youth Criminal System, and its educational intend. This, in the context of the substitution and modification of the first instance incarceration decision in Bogotá, Colombia. The text will provide an overview of the doctrine and jurisprudence on the matter and contrast it with the judicial practices found on the first instance courts. The knowledge on these judicial practices was gathered by conducting eight semi-structured interviews to judges that are firsthand experts on the matter. In conclusion, it was found that first instance practices differ from the findings in the doctrine and jurisprudence of the high courts, which questions the system as a differentiated system from the one established for adults.